Thermal condition in a tunnel brick kilning kiln with vocculated burners - D. B. Vafin; A. A. Mukatdarov; D. A. Mukatdarova (Известия высших учебных заведений: Проблемы энергетики)
Despite the large volume of large-panel and monolithic construction in modern cities, the level of aesthetic requirements for house construction using new finishing building materials also leads to an increase in the demand for ceramic bricks. To solve the problem of the national project “affordable housing” it is necessary to increase the production of locally produced ceramic bricks. To do this, it is necessary to modernize existing brick factories or build new ones. In this case, it is desirable to use new technologies and production methods that ensure the quality of the produced bricks. The properties of bricks are mainly formed during the firing process, which at the same time is the most complex and heat-intensive production stage. The required quality of building ceramics largely depends on ensuring a certain temperature distribution during the firing process while moving cars with bricks along the tunnel kiln. Therefore, work devoted to ensuring the required temperature distribution in different zones of tunnel furnaces with different placements of gas burners is relevant from a practical point of view.THE PURPOSE of the work is to experimentally determine the temperature in different places of the tunnel furnace volume during the movement of the car in the operating furnace.METHOD. Temperature sensors with remote information transmission were placed on the brick cages of a carriage moving along the kiln, the signals from which were recorded by a multi-channel meter during the entire firing cycle. The measurement results are presented in the form of graphs of temperature dependences from various sensors depending on the time of the firing process. Based on the results of the experiments, conclusions were drawn regarding improving the quality of heat treatment of bricks and reducing production defects.